Pengaruh Motivasi dan Pelatihan Kerja terhadap Kinerja Pegawai pada Sekretariat Dinas Perhubungan Kabupaten Bogor - Adhar, Andi Muhammad; Taat Kuspriyono; Yunidyawati Azlina (Jurnal Manajemen Bisnis Era Digital, 2025)
In the era of globalization and increasingly tight competition, employee performance is one of the determining factors for the success of public services and the implementation of government work programs. Therefore, the quality of human resources owned plays a very important role in supporting the success of the organization, including in the Bogor Regency Transportation Service environment. This study was conducted against the background of indications of problems in motivation and job training at the Bogor Regency Transportation Service Secretariat. This study uses associative statistical quantitative methods. Data were collected through questionnaires distributed to 40 respondents with total sampling techniques. Data analysis was carried out using SPSS software version 23, primary data collection through questionnaires and secondary data from journals and relevant scientific works. The data obtained were then analyzed through validity tests, reliability, multiple linear regression, T tests, F tests, and coefficient of determination tests. The results of the study showed that motivation has a significant positive effect on employee performance, with a t-count value of 3.988 and a significance of 0.000. And also, job training has a significant positive effect on employee performance, with a t-count value of 5.694 and a significance of 0.000. Simultaneously, motivation and work training together influence employee performance by 74.5%, while the remaining 25.5% is influenced by other variables not discussed in this study.